Oblicza człowieka masowego — od totalitaryzmu do konsumpcjonizmu - Kaczor, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article presents two figures of mass society that emerged in the twentieth century. The former revealed itself in the era of totalitarianism, while the latter resulted in the emergence of a consumer society. Neither of these figures are a necessary consequence of the processes leading to the rise of the masses as a social phenomenon. They have been created as a result of specific historical conditions. Consequently, mass society can take on any of these forms. They are also not disjoint, which means that authoritarian attitudes and consumer behavior can occur simultaneously. The relationship between the described attitudes adopted by the mass man occurs at the level of their attitude to freedom and democratic institutions. Modernity has resulted in the fact that the individual cannot cope with the freedom they gained as a result of being freed from tradition and religion. If they cannot free themselves an authority to show them how to live. This authority may also be of a group nature. Belonging to a specific community gives an individual a sense of bond and security. Freedom in a consumer society is primarily the freedom to choose consumer goods. In any case, democracy is not a valued form of managing society. Before the rise of totalitarianism, it did not ensure sufficient coherence and a sense of participation. At the same time, in the consumer society, its basic procedures began to trivialize and become part of marketing mechanisms.
Keywords: społeczeństwo masowe; społeczeństwo konsumpcyjne; totalitaryzm; autorytaryzm; wolność; demokracja